2020
DOI: 10.3390/nu12051537
|View full text |Cite
|
Sign up to set email alerts
|

Salt Taste, Nutrition, and Health

Abstract: The sodium ion (Na+) is essential for life [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
1
10
0
1
Order By: Relevance
“…Animal models showed that the sodium-specific and amiloridesensitive epithelial sodium channel (ENaC) and the transient receptor potential cation subfamily V member 1 (TRPV1) amiloride insensitive channel are candidates for the pathway of salty taste. (Bigiani, 2020) The results of this study support this evidence as association between variants (noncoding rs12162045 and rs152733 in SCNN1B gene, OR = 0.455 and OR = 1.835, respectively; synonymous rs877610, noncoding rs8078936 and rs150908 in TRPV1 gene) and saltiness preference was observed. There is a lack of evidence for SCNN1A and SCNN1G genes being associated with saltiness and the involvement of these proteins in salty taste pathway in humans.…”
Section: Discussionsupporting
confidence: 79%
“…Animal models showed that the sodium-specific and amiloridesensitive epithelial sodium channel (ENaC) and the transient receptor potential cation subfamily V member 1 (TRPV1) amiloride insensitive channel are candidates for the pathway of salty taste. (Bigiani, 2020) The results of this study support this evidence as association between variants (noncoding rs12162045 and rs152733 in SCNN1B gene, OR = 0.455 and OR = 1.835, respectively; synonymous rs877610, noncoding rs8078936 and rs150908 in TRPV1 gene) and saltiness preference was observed. There is a lack of evidence for SCNN1A and SCNN1G genes being associated with saltiness and the involvement of these proteins in salty taste pathway in humans.…”
Section: Discussionsupporting
confidence: 79%
“…Salt is necessary for human health, consisting mainly of sodium chloride (NaCl) [13]. One sodium chloride molecule represents a 1:1 sodium (Na + ) and chloride (Cl − ) ions ratio.…”
Section: The Interplay Between Sodium Intake and Blood Pressurementioning
confidence: 99%
“…At a dose of 0.1 g/mL, it was difficult to appreciate chemosensory differences in the taste dimensions of the saline solutions due to the high concentrations used, thus our attention was focused on low doses (0.04 g/mL). In the literature it is known that salt at medium-low concentrations is usually perceived as pleasant and palatable [ 1 ], while at high doses it activates aversive taste pathways [ 36 ]. In fact, in our study, for patients with hyposmia at the dose of 0.04 g/mL it was possible to evaluate more accurate differences in salty perception.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the body’s homeostasis is strictly related to salt (sodium chloride, NaCl) [ 1 ]. An increased salt intake is considered a risk factor for hypertension, stroke, and high blood pressure [ 2 ].…”
Section: Introductionmentioning
confidence: 99%